Field And Laboratory Evaluation Of Degradation, Leaching, Stability In Storage And Bioavailability Of Soil Termiticides On The Asian Subterranean Termites, Coptotermes gestroi (Blattodea: Rhinotermitidae) - Rashid, Mohd Fawwaz Mohd (2018)
Soil termiticide treatment is a fundamental method to control termite population and infestation by creating a continuous barrier surrounding the structures. However, termiticides may dissipate, depending on a half-life, a degradation rate, a leaching activity and a storage method. In this study, the degradation rate and half-life of three commercially available termiticides, namely Maxxthor 100 SC (bifenthrin), Chalcid 5.0 SC (fipronil) and Prothor 200 SC (imidacloprid) were determined under the field and laboratory conditions. Fipronil showed the most persistent termiticide in the field study as it had a lower degradation rate (top= 4.19 ppm/day; bottom= 4.06 ppm/day) and a higher half-life (top= 267.99 days; bottom= 282.56 days).